Thermo-electrochemical simulation of the cooling process in a compact battery pack considering various configurations - Pordanjani, Ahmad Hajatzadeh; Aghakhani, Saeed; Afrand, Masoud; Zhang, Ping; Tang, Rongjiang; Mahian, Omid; Wongwises, Somchai; Rashidi, Mohammad Mehdi (Journal of power sources)
Lithium-ion battery (LIB) packs with high power density are necessary in battery-powered system development. In this study, we investigated LIB packs made of compact cylindrical Li-ion batteries. We arranged the batteries in various patterns, including square, lozenge, elliptical, and circular, with all patterns occupying the same total area. We solved the thermal and electrochemical equations governing the batteries using the finite-element method (FEM), and we coupled the airflow around the batteries, meant to lower their temperature, with the LIB equations and solved them using the same method. The results reveal that LIB cooling enhancement and a smaller temperature gradient occur with an increase in the LIB distribution at the center, reducing their outward dissemination and shortening the LIB length. Additionally, increasing the cross-sectional area and airflow velocity enhanced heat transfer from the batteries and decreased their temperature. Finally, we demonstrated that better cooling enhances the cells’ long-term performance. With a circular configuration, the pressure drop and heat transfer rise by 48.01% and 85.14%, respectively, with an increase in the inlet cross-section area. Furthermore, the pressure drop and heat transfer in this configuration increased by 89.09% and 66.90%, respectively, when the velocity increases.